Articulate Storyline with Augmented Reality to Enhance Students Language Proficiency at Satap Besakolka - Diana Fallo; Hanna M. Baun (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
Enhancing the quality of education in the digital era faces challenges, particularly in remote areas such as SATAP Besakolka in the South-Central Timor Regency. The low English proficiency among students in this region is often attributed to limited access to interactive, technology-based learning resources, leading to decreased motivation and poor learning outcomes. To address this gap, an innovative learning medium is required to capture student interest and facilitate comprehension effectively. This study aims to develop and empirically test the effectiveness of a learning medium that integrates Articulate Storyline with Augmented Reality (AR) technology. Specifically, this research was designed to measure the significant difference in students' English abilities before and after the intervention and to determine the level of the medium's effectiveness in improving learning outcomes. This research employed a quantitative method with a Pre-Experimental One-Group Pretest-Posttest design. The subjects were 30 third-grade students at SATAP Besakolka, selected using a simple random sampling technique. Data was collected through an objective test (multiple-choice) administered as a pretest and posttest, with the instrument having undergone expert validity testing. The collected data were statistically analyzed using the Paired Sample t-Test for the hypothesis and the Normalized Gain Score (N-Gain) to measure effectiveness. The data analysis revealed a statistically significant improvement in students' English language abilities. The Paired Sample t-Test yielded a significant value of 0.000 (p < 0.05), confirming a tangible difference between the pretest and posttest scores. Furthermore, the N-Gain calculation resulted in a score of 0.6912, indicating that the improvement in student learning outcomes falls within the